Experimental demonstration of optical Brownian ratchet by controllable phase profile of light. (October 2021) - Tang, Xionggui; Shen, Yi; Xu, Yanhua
Research highlights: An optical Brownian ratchet by using phase gradient profiles is proposed and experimentally demonstrated. The phase profiles and intensity distributions in optical traps can be accurately created by the designed holograms, which are very important for achieving Brownian ratchet motion. The optical Brownian ratchet exhibits excellent performance in optical nanomanipulation, which largely expands the capacity of conventional Brownian ratchet that rely on the intensity gradient force. Abstract: Brownian ratchet has emerged as a promising tool for deeply understanding motion mechanism of molecules and proteins, and dynamically manipulating particles in non-equilibrium thermodynamics state. Here, we propose and experimentally demonstrate a new type of optical Brownian ratchet, as generated by controllable phase profiles in holographic optical trapping system. The potential energy profiles are dynamically switched in on-off mode, by using Labview software. Experimental results show that not only high speed but also large step distance can be easily achieved in Brownian ratchet, in which the average velocity of forward motion is around 28 μm/s and step distance is about 42 μm. Importantly, the velocity, step distance and motion path can be easily adjusted by manipulating the holograms, which exhibit high flexibility, easy control and excellent capability. This study provides a new way to explore non-equilibrium dynamics at the nanoscale level, and create novel functions in nanoparticle manipulation.